The Inner Workings of the Outer Surface: Skin and Gill Microbiota as Indicators of Changing Gut Health in Yellowtail Kingfish - Legrand, Thibault P. R. A.; Catalano, Sarah R.; Wos-Oxley, Melissa L.; Stephens, Fran; Landos, Matt; Bansemer, Matthew S.; Stone, David A. J.; Qin, Jian G.; Oxley, Andrew P. A. (Frontiers in Microbiology, 2018)
The mucosal surfaces and associated microbiota of fish are an important primary barrier and provide the first line of defense against potential pathogens. An understanding of the skin and gill microbial assemblages and the factors which drive their composition may provide useful insights into the broad dynamics of fish host-microbial relationships, and may reveal underlying changes in health status. This is particularly pertinent to cultivated systems whereby various stressors may led to conditions (like enteritis) which impinge on productivity. As an economically important species, we assessed whether the outer-surface bacterial communities reflect a change in gut health status of cultivated Yellowtail Kingfish (Seriola lalandi). Active bacterial assemblages were surveyed from RNA extracts from swabs of the skin and gills by constructing Illumina 16S rRNA gene amplicon libraries. Proteobacteria and Bacteroidetes were predominant in both the skin and gills, with enrichment of key β-proteobacteria in the gills (Nitrosomonadales and Ferrovales). Fish exhibiting early stage chronic lymphocytic enteritis comprised markedly different global bacterial assemblages compared to those deemed healthy and exhibiting late stages of the disease. This corresponded to an overall loss of diversity and enrichment of Proteobacteria and Actinobacteria, particularly in the gills. In contrast, bacterial assemblages of fish with late stage enteritis were generally similar to those of healthy individuals, though with some distinct taxa. In conclusion, gut health status is an important factor which defines the skin and gill bacterial assemblages of fish and likely reflects changes in immune states and barrier systems during the early onset of conditions like enteritis. This study represents the first to investigate the microbiota of the outer mucosal surfaces of fish in response to underlying chronic gut enteritis, revealing potential biomarkers for assessing fish health in commercial aquaculture systems.